Maternal plasma fetal DNA fractions in pregnancies with low and high risks for fetal chromosomal aneuploidies. - Irena Hudecova; Daljit Sahota; Macy M S Heung; Yongjie Jin; Wing S Lee; Tak Y Leung; Yuk Ming Dennis Lo; Rossa W K Chiu (PLoS ONE)
Recently published international guidelines recommend the clinical use of noninvasive prenatal test (NIPT) for aneuploidy screening only among pregnant women whose fetuses are deemed at high risk. The applicability of NIPT to aneuploidy screening among average risk pregnancies requires additional supportive evidence. A key determinant of the reliability of aneuploidy NIPT is the fetal DNA fraction in maternal plasma. In this report, we investigated if differences in fetal DNA fractions existed between different pregnancy risk groups. One hundred and ninety-five singleton pregnancies with male fetuses divided into 3 groups according to first trimester screening parameters were examined for fetal DNA percentage by counting Y chromosome DNA sequences using massively parallel sequencing. Fetal DNA fractions were compared between risk groups and assessed for correlations with first trimester screening parameters. There was no statistically significant difference in fetal DNA fractions across the high, intermediate and low risk groups. Fetal DNA fraction showed a strong negative correlation with maternal weight. Fetal DNA fraction also showed weak but significant correlations with gestational age, crown-rump length, multiple of medians of free β-subunit of human chorionic gonadotropin and pregnancy-associated plasma protein A. Similar fetal DNA fractions in maternal plasma between high, intermediate and low risk pregnant women is a precondition for uniform performance of the aneuploidy NIPTs for the general population. This study thus shows that the aneuploidy screening by NIPT is likely to offer similar analytical reliability without respect to the a priori fetal aneuploidy risk.